A Scenography research of Mindanao indigenous dance and rituals in the context of its vernacular architecture - Catog, Genevieve (2014)
The idea of studying environment as a simulator to understand a dance ritual is the main motivation of this research. Mindanao indigenous dance rituals have the strong concept of using its environment as an inspiration to synthesize and choreograph a dance. With this reason, there?s a need to explore and study this environment(s) in order to synthesize a performance space that produces spatial communication, awareness and experience. By the use of scenography, as the process of understanding an environment of a performance; every spatial component, element and any factor present in the performance was systematically analyzed in order to show how it supports the whole idea of the dance ritual. This study mainly used photo and video documentations and interviews from on-site performances of Mindanao indigenous dance and rituals. It was interpreted and analyzed by several methods such as architectural drawings, video abstraction, shift plots, field notations and etc. this research covered six indigenous dances from different ethnolinguistics groups in Mindanao. On the six study areas in Mindanao, this research studied the scenography of madal Tahaw of T?boli, Aral Del mof B?laan, Binagabo Dance of Bagobo, Singkil of Meranao, Madayaw na Pagdatung of Mandaya, and Sayaw sa Saluray of Kudlong of Matigsalug. Each of these dances was documented on site supplemented with interviews and descriptions from heads of the tribal council or art director of Visual Communications studies from Mindanao State University, Marawi campus. From space management, construction acoustics, and lighting, these factors should be utilized well in order to produce such a scenic design that houses these dance rituals? realistic setting. With the smallest (5.20 sq.ntr.) to largest (292.00 sq.mtr.) scenic areas of these dances, performance sets should be associated to the choreography, performing bodies and number of actual audience. Intimate (0.00m-0.44m), social (0.44m-3.59m), and public (3.6 above) distance between scenic objects and performing bodies evidently show how these dances use representations and perceptions to their environment. Acoustal scenography of the indigenous dances should both consider the sequence and location of the musical instruments and ecological sounds. Lighting conditions such as night (0ux-5lux), overcast (5lux-20lux), and clear sky (102lux and above). Should be translated in theatrical lighting in order to interpret the time settings and environment of the scene. Findings and conclusions of this research shows that the on-site performance set of these dances essentially support and related its context. Therefore, the scenography of Mindanao indigenous dance and rituals should visually represent its context, deliver spatial experience to the site, and provide a functional performance space with respect to its choreography, culture, and architecture.